Engagement in Online Newspaper Articles Written by Female Authors - WALIDA WAHID FITRIANI (Universitas Pekalongan, 2023)
Newpaper articles demand a link between the readers and the authors. They engage their readers by presenting several convincing clauses yet objective. Furthermore, they frame the authors’ position in the text. So that the readers will follow the authors’ flow. They wrap them all in an Appraisal Framework Theory proposed by Martin and White (2005). Gender and psychological theories from Shields (2000), Coates (2016), and Guimond (2008)are considered. This study is aimed to explore the manifestation of engagement in online newspaper articles written by female authors. It employed descriptive qualitative method in the form of discourse study analysis. It analyzed eight articles taken from three well-known newspaper websites. The findings revealed that the eighth authors mostly employed heterogloss clauses. Female authors mostly use disclaim clauses. There was 47,9% of the whole clauses indicate disclaim. Meanwhile, clauses or utterances which indicate personal/internal subjectivity (author’s opinions) or entertain were 22,5%. Clauses that indicate external subjectivity or entertain were 21,1%. The fewest distribution was proclaim clauses which were only 8,5%. This study contributes in English teaching learning. Since it helps beginner writers to engage the link between readers and authors by presented clauses and utterances. Keywords: Engagement, Newspaper, Articles, Female, Authors